Effect of following-up nursing guided by timing theory on rehabilitation and quality of life of elderly patients with acute myocardial infarction treated with percutaneous coronary intervention (时机理论引导的跟踪式护理对老年AMI患者PCI术后康复及生存质量的影响) - Zhang Keke (张珂珂) (中西医结合护理)
Objective To explore the effect of following-up nursing guided by timing theory on rehabilitation and quality of life of elderly patients with acute myocardial infarction (AMI) after percutaneous coronary intervention (PCI) . Methods Totally 96 elderly AMI patients treated with PCI were randomly divided into two groups, with 48 cases in each group . The control group was given routine follow-up nursing after discharge from hospital, and the study group was given the following-up nursing guided by timing theory. The parameters of cardiopulmonary exercise test, the results of 6-min Walking Test(6MWT), the incidences of major adverse cardiovascular events (MACE), the quality of life were compared between the two groups. Results There was 1 case of cardiac death in the study group and 3 cases of cardiac death in the control group during follow-up. After nursing, the peak power output, peak exercise oxygen consumption, peak minute ventilation volume and 6MWT distance of the two groups were higher than those before nursing (P<0. 05), which in the study group were higher than those in the control group (P<0. 01). The incidence of MACE in the study group was lower than that in the control group (P<0. 05). After nursing, the scores of 8 dimensions of SF-36 Health Survey in the two groups were higher than those before nursing (P<0. 05), which in the study group were higher than the control group (P < 0. 05). Conclusion The implementation of follow-up nursing guided by timing theory in elderly patients with AMI treated by PCI can not only enhance cardiopulmonary function and exercise endurance, but also improve the quality of life. (目的 探讨时机理论引导的跟踪式护理对老年急性心肌梗死(AMI)患者经皮冠脉介入治疗(PCI)术后康复及生存质量的影响。方法 将96例AMI实施PCI术后出院的老年患者随机分为对照组和研究组, 各48例。对照组实施常规跟踪式护理, 研究组实施时机理论引导的跟踪式护理。比较2组护理前后心肺运动试验参数、6 min步行试验(6MWT)结果, 记录护理期间主要不良心血管事件(MACE)发生情况, 评估患者生存质量。结果 研究组护理期间有1例心源性死亡, 对照组有3例心源性死亡。干预后2组峰值功率、峰值耗氧量、峰值分钟通气量、6MWT距离均较干预前提高(P＜0. 05), 且研究组较对照组改善明显(P＜0. 01)。研究组MACE发生率低于对照组(P＜0. 05)。干预后2组简明生活质量量表的8个维度评分均较护理前提高(P＜0. 05), 且研究组较对照组改善明显(P＜0. 05)。结论 对老年AMI患者PCI术后实施时机理论引导的跟踪式护理, 不仅有助于增强心肺功能和运动耐力, 减少MACE发生风险, 还能提升生存质量。)